Identification of Endogenous Antagonistic Bacteria in Grape Leaves and Its Inhibitory Effect on Postharvest Aspergillus niger in Thompson Seedless Grapes - Miaomiao ZHANG; Yizhong YANG; Yuchen ZHANG; Jie MA; Zhenzhen XU; Wei WANG; Lijuan ZHANG; Ning WANG; Yingying FAN; Cheng WANG; Wei HUANG; Fengjuan LIU (Shipin gongye ke-ji)
To screen endophytic strains with strong antibacterial activity from grape leaves and assess their biocontrol potential, providing a theoretical basis for the development of new biological control strategies against grape Aspergillus rot disease. Using the plate confrontation method, antagonistic strains displaying notable inhibitory effects on Aspergillus niger were isolated from the leaves of 'Thompson Seedless Grapes'. Morphological, physiological, biochemical, and molecular-biological analyses identified the antagonistic strains to species-level resolution. Lipopeptide extracts from the fermentation supernatant were analyzed by UPLC-Vion-IMS-QTof mass spectrometry, revealing their chemical composition. In vivo experiments further confirmed the efficacy of the antagonistic fermentation broth in reducing postharvest Aspergillus rot on 'Thompson Seedless Grapes'. From the leaves of 'Thompson Seedless Grapes', 25 endophytic bacterial strains with inhibitory effects on A. niger were isolated. Among these, strain TLF4-3 demonstrated the strongest antagonistic activity, exhibiting an inhibition zone diameter of 27.27±0.05 mm and an inhibitory titer of 18.27±0.53 cm/mL. UPLC-Vion-IMS-QTof analysis identified the primary antimicrobial compounds produced by this strain as bacillomycin D2 (C15) and iturin C (C14). Treatments with TLF4-3 fermentation broth at 3 days postharvest achieved the best control effect, reducing lesion diameter by 2.3 mm and achieving an antibacterial rate of 68.26%±0.91%. These results offer a theoretical framework and pragmatic direction for the control and avoidance of Aspergillus rot in postharvest grapes.